Aplikasi Sistem Layanan Sekolah SMA XYZ Berbasis Mobile Device dan Service Oriented Architecture - Setiawan, Arif Priyata; Handojo, Andreas; Palit, Henry Novianus (Jurnal Infra, 2016)
XYZ High School is a private high schools that was founded in 1959 and has more than 500 students. On daily basis, XYZ high school conducts the recording and sharing of data manually. Since the recording is done manually, XYZ High Schoolâs paper usage is considerably high and often it finds difficulties in finding data because they are stored in the non digital-archive . This thesis developed web and mobile devices - based application acting as a service system that provides information related to students and teachers .This service system has features to display information about the academic data such as the studentâs score and the teaching materials that can be downloaded by the students, and the non-academic data such as personal information of students, personal information of teachers, class schedule, announcements, and information about violations committed by students.The test results show that the system can help the student to search the information and operate well in a variety browsers and Android devices